PEROLEHAN GLUKOSA DENGAN HIDROLISIS ENZIMATIS DARI AMPAS TEBU MENGGUNAKAN Trichoderma viride DAN Aspergilus niger SEBAGAI BAHAN BAKU BIOETANOL - Sari, Elita; Rahman, Elly Desni; Martynis, Munas; Fiona, Shafira; -, Junialdi (Universitas Andalas, 2015)
Lignocellulosic biomass is a rich agricultural waste containing cellulose and hemicellulose. Bagasse (bagasse) is one of the waste biomass containing cellulose and hemicellulose approximately 47.7% which can be used to produce bioethanol. Enzymatic process is able to hydrolysis the polysaccharide compound into its constituent, sugars monomer compound. An enzymatic hydrolysis process converts cellulose to glucose by using cellulase enzymes. Some microorganisms producing the enzyme cellulase are Trichoderma viride and Aspergillus niger. The purpose of this research is to find out comparison of both these microorganism as a catalyst in the enzymatic hydrolysis process that produces the highest glucose levels and hydrolysis time. Hydrolysis process is done by varying the ratio between Tricoderma viride and Aspergillus niger of 1: 0; 0: 1; 0.5: 1 and 1: 0.5 and time sampling 24, 48, 72, 96, 120. The results showed glucose acquisition as much as 360 mg/L with hidrolysis process by hotplate stirer and 660 mg/L with process by waterbath shaker at composition ratio of Trichoderma viride: Aspergillus niger 1: 0.5 and the hydrolysis time is 96 hours.